(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to develop a valid and practical learning model, namely the Distar Learning Model, to improve students’ collaboration skills. This research is a type of Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), and was conducted in the odd semester of the 2024/2025 academic year at SMA Negeri 9 Gowa. The research subjects were 36 students of class XII MIPA 5. The validation results showed that the guidebook obtained a feasibility score of 87.16% (feasible for use), teaching materials 88.6% (very valid), learning modules 94.16% (very valid), and the Student Worksheet (LKPD) obtained a score of 3.77 out of 4.00 (very valid). The practicality test showed that the model had an implementation success rate of 90.47%. These findings indicate that the Distar Learning Model is proven to be valid and practical, and has the potential to improve students’ collaboration skills. This model is recommended for broader implementation to facilitate 21st-century learning that emphasizes collaboration and active student engagement. Keywords: Learning Model, Collaboration Skills, 21st Century Learning, Distar Learning